Leben ist Schwingung, ist Fuge: Hannah Arendt über Arbeiten, Natur und politische Ökologie - Doğan, Caner (HannahArendt.net, 2025)
This article deals with Hannah Arendt’s understanding of labor as a fundamental form of human activity with regard to experiences of nature. To this end, I first discuss the specific phenomenological method that Arendt uses to develop her own concept of labor, in which she integrates und differentiates central topics of Karl Marx’ philosophy of labor. In the following step, the concepts of swinging and fugue are outlined and developed, which can be understood as fundamental experiences of nature made by human beings while laboring. With these concepts and a specific look at Arendt's elaborated or implied descriptions of experiences of nature, I will take a look at current debates of political ecology. In particular, references will be made to Jane Bennett’s concept of Vibrant Matter, Donna Haraway’s sympoiesis and Bruno Latour's descriptions of the earth as Gaia. It can thus be shown that Arendt sees and develops concepts to describe the experiences made by human beings while laboring that are central to a central concern of all authors of political ecology, namely dismantling the strict boundaries between the human world and the natural world for the reason to gain a different view on the being-in-the-world of modern humans.